2018
DOI: 10.4081/jphr.2018.1443
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Information in Mandatory Reporting in Victims of Gender Violence

Abstract: The healthcare professional plays a key role in the detection and subsequent channeling of a situation of violence to a judicial level for appropriate investigation. The mandatory reporting of gender violence has become a controversial issue among health care practitioners and victims. The objective of this study was to analyze the quality of the way in which injury reports on victims of gender violence is completed, through an analysis of the information they include, the readability and the degree to which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Violence against women, or gender-based violence (GBV), is a global serious public health problem [ 1 , 2 , 3 ]. Almost 18% of women and girls aged 15 to 49 years who have ever been in a relationship have experienced physical or sexual violence by an intimate partner in the previous 12 months [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Violence against women, or gender-based violence (GBV), is a global serious public health problem [ 1 , 2 , 3 ]. Almost 18% of women and girls aged 15 to 49 years who have ever been in a relationship have experienced physical or sexual violence by an intimate partner in the previous 12 months [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A Spanish retrospective study analyzing 197 clinical records related to DV revealed multiple errors: unreadable or missing information, namely victims’ personal data and doctors’ identification. In 7.1% of the cases, victims’ identification was not possible based on clinical records [ 36 ]. This unsatisfactory quality of clinical records compromises any potential future juridical process.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the signs that can guide us about the possibility of unreported violence are the presence of injuries in hidden places, the characteristics of the injuries (stage of evolution, defense injuries), repetition in consultations, confusing or incoherent reports in the anamnesis about the mechanism of injury and attitudes of rejection or mistrust during the examination and non-specific and indirect indicators of depression, agitation or emotional lability (Blanco et al, 2004;Osuna et al, 2009;Rivadeneira, 2017). In this regard, it is important to highlight the importance of completing the injury report that allows the judicial investigation and the channeling of the victim towards the available health and social resources (Reynaldos, 2018). We must not forget that gender violence encompasses other types of abuse such as psychological, sexual or economic, and it is common for different manifestations to coexist.…”
Section: Introductionmentioning
confidence: 99%